SIMBOLISME AGAMA DALAM NOVEL THE SATANIC VERSES: PERSPEKTIF SEMIOTIKA FERDINAND DE SAUSSURE - Muhammad Alfarryzy; Amalia Rahma Karulin; Anisah Harissahdini (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
Semiotics is a field of science that examines symbols in an object. The novel The Satanic Verses by Salman Rushdie is the fourth work in the style of magical realism. The purpose of this study was to determine religious symbolism based on the perspective of Ferdinand de Saussure in the novel The Satanic Verses by Salman Rushdie. This research uses a qualitative descriptive research method. The collection of data in the novel The Satanic Verses uses reading and note-taking techniques. Based on the results of the analysis that has been carried out, found seven data on religious symbols were found consisting of Mahoud, Jibril, Abraham, Satanic verses, the use of the names of the Prophet Muhammad's wife (Saudah, Ayesha, Hafsah, Umm Salamah the Makhzumite, Rumlah, Zainab bint Jahsh , Juwairiyah, Rehana the Jew, Safia, Maimunah, Mary the Copt, Zainab bint Khuzaimah). The results of the analysis show that the writer takes an ahistorical figure from the writer's imagination.